Environmental sustainability in sport: a systematic literature review. Issue 1 (2nd January 2023) - Cury, Rubiana; Kennelly, Millicent; Howes, Michael
ABSTRACT: Research question: How are bibliographic and methodological patterns, as well current contributions of environmental sustainability in sport literature, shaping a research agenda that informs effective environmental responses? Research methods: This study surveys previous literature reviews. It then combines a systematic quantitative literature review and meta-synthesis to determine bibliographic, methodological and theoretical patterns of literature and to assess the key contributions and knowledge gaps. Results and Findings: Limitations in the scope of previous literature reviews established the need for a more comprehensive examination of knowledge in the field. This systematic review identified environmental sustainability in sport as an emerging field with predominantly North American (in terms of both authorship and geographical settings) studies. Contributions on management and governance of environmental initiatives, shifts in environmental discourses, environmental education in sport contexts, and environmental sustainability through sport are discussed with the purpose to set directions for future research. Implications: The international urgency and complexity of environmental issues necessitate the adoption of a global perspective and research approaches that enable sport researchers and practitioners to collaborate closely on knowledge development. Future research may expand on existing managerial and environmental education contributions and explore new theoretical terrains to advance knowledge on environmental policy and innovative approaches for effective design and implementation of sport industry's environmental responses.